2001
DOI: 10.1002/pat.88
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of heteroarm star‐branched polymers by means of anionic living polymerization

Abstract: The synthesis of well-defined three-and five-arm star polymers, with varying arm lengths, was described by the method based on anionic living polymerization. A three-arm AB 2 star polymer was synthesized by the linking reaction of a specially designed two chloromethylphenyl-end-functionalized polystyrene prepolymer with the anionic living polymer of t-butyl methacrylate initiated with diphenylmethylpotassium. A five-arm AA' 2 B 2 star polymer was synthesized by the linking reaction of the same functionalized p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…In our previous paper, it was observed that the chloromethylated polystyrene was not reacted in THF at -78 8C for 168 h with the living anionic polymer of t BMA prepared by the diphenymethyllithiuminitiated polymerization in the presence of LiCl. [28] On the other hand, the reaction proceeded quantitatively under the same conditions with the living polymer of t BMA prepared by the polymerization with diphenylmethylpotassium. The living anionic polymer of t BMA having potassium counter cation was therefore employed in the reaction with poly(m-halomethylstyrene)s.…”
Section: Synthesis Of Well-defined Graft Copolymers With One Graft Pementioning
confidence: 91%
“…In our previous paper, it was observed that the chloromethylated polystyrene was not reacted in THF at -78 8C for 168 h with the living anionic polymer of t BMA prepared by the diphenymethyllithiuminitiated polymerization in the presence of LiCl. [28] On the other hand, the reaction proceeded quantitatively under the same conditions with the living polymer of t BMA prepared by the polymerization with diphenylmethylpotassium. The living anionic polymer of t BMA having potassium counter cation was therefore employed in the reaction with poly(m-halomethylstyrene)s.…”
Section: Synthesis Of Well-defined Graft Copolymers With One Graft Pementioning
confidence: 91%
“…Furthermore, we have recently synthesized a nine-arm AA9 4 A99 4 asymmetric star polystyrene in A 95% yield by using a polystyrene end-functionalized with four CMP groups as illustrated in Scheme 19. [54] The results are summarized in Tab. 10.…”
Section: Synthesis Of Heteroarm Star Polymers Using Cmp Multi-functiomentioning
confidence: 96%
“…[49,50] Furthermore, several regular, asymmetric and heteroarm star polymers were synthesized by using a variety of CMP-functionalized polystyrenes and polystyrene-block-poly(a-methylstyrene)s. The synthesized polymers were stars of the AA9 3 , AA9 4 , AA9A99 2 , AB 3 , AB 4 , A 2 B 4 , A 2 B 12 , ABC 2 , and ABC 4 types where A, B, and C are polystyrene, polyisoprene, and poly(a-methylstyrene), respectively. [49,51,52] Coupling reactions with direct use of poly(styryllithium) or poly(isoprenyllithium) usually proceeded along with the formation (a10%) of star polymers having less arms. This strongly indicates that undesirable side reactions, such as Li1Cl exchange and single-electron transfer reactions, take place during the coupling reactions to a certain extent.…”
Section: Synthesis Of Heteroarm Star Polymers Using Cmp Multi-functiomentioning
confidence: 99%
“…98,111 In these coupling reactions, benzyl bromide functionality is more preferable than the chloride counterpart. The results are summarized in Table IV. Thus, the proposed coupling reaction with use of benzyl halide-functionalized polymers offers a new general and versatile methodology for the synthesis of both regular and star polymers with well-defined architectures.…”
Section: Coupling Reaction Of Living Anionic Polymers With Benzyl Halmentioning
confidence: 99%
“…[95][96][97][98] These benzyl halidefunctionalized polymers are used as polymeric coupling agents in the reaction of living anionic polymers.…”
Section: Synthesis Of Star Polymers Using Benzyl Halide-functionalizementioning
confidence: 99%